Analisis Komparatif Kualitas Pelayanan Nasabah Pengguna Aplikasi Digital Dan Manual Pada Pegadaian Syariah Sidrap - Wardani, Safira; Soumena, Moh Yasin; Musmulyadi, Musmulyadi; Subair, Muhammad Kamal; Budiono, I Nyoman (SEIKO : Journal of Management & Business, 2023)
The presence of the Digital Sharia Pegadaian Application is not only able to save customers' time in making transactions, but customers also get many other advantages and benefits. In line with technological developments, the majority of Pegadaian Syariah Sidrap customers receive manual transaction services. The aim of this research is to find out the comparative comparison of users of the Pegadaian Syariah Digital and Manual application services. This research uses a qualitative approach and collects data using a field research approach. The data analysis technique used is a qualitative interactive analysis technique. The research results found that users of online and manual services at Pegadaian Syariah Cab. Sidrap, customer of Pegadaian Syariah Cab. Sidrap still uses a lot of manual services compared to online services, only ten persen of the results of interviews with service users via the Pegadaian Syariah Digital application compared to manual services. Due to the lack of customer understanding of the Digital Sharia Pawnshop application and the institution's outreach to customers is still lacking. Keyword : Comparative, Service Quality, Online, Sharia Pawnshop.